Pendampingan dan Penguatan Kapasitas Masyarakat dalam Pemulihan Kerusakan Lingkungan di Provinsi Sulawesi Barat - Andi Ridha Yayank Wijayanti; Kaimuddin Kaimuddin; Muhammad Arafat Abdullah; Nurlaela Nurlaela; Astina Astina; Andi Arafat; Firmasyah Bin Abd Jabbar; Nurfaizi Nurfaizi (Universitas Muhammadiyah Surakarta, 2024)
Community empowerment begins with understanding that every individual and group has potential and abilities that can be developed. In Mamuju Regency, precisely in Tommo District, there is peat but it is small which if damaged and not managed properly will result in land fires, floods, and soil pollution. This assistance aims to position the community as a party that plays an active role in environmental recovery. One of the initial stages of assistance or empowerment activities carried out is Problem Identification and Situation Analysis. It is hoped that the problems faced can be clearly identified, the related situation can be analyzed comprehensively, and the next steps can be designed to plan effective and sustainable interventions. Strengthening the understanding of problem identification and location analysis is carried out using the IMAS tool through survey methods, interviews, and FGDs. The results of problem identification and situation analysis found several problems that can be used as references in formulating systematic and effective planning for community empowerment. Based on the results of the problem identification and situation analysis in Buana Sakti Village, Tamemongga Village, Tamejarra Village, West Leling Village and North Leling Village, problems were found in flooding, lack of fertilizer availability and the distance of the village from the city which makes it difficult to get fresh fish to meet the protein needs of the community. From the results of the problem identification and situation analysis, a Community Work Plan formulation was formed such as freshwater fish farming, long-term crop planting, horticultural planting, and livestock farming. The proposed work plan is expected to be able to help the community in meeting needs, improving the community's economy, and can answer problems that occur in each village.